A case of ocular tuberculosis presenting as papillophlebitis - Mughaddasifar, Hossein; Ramezani, Alireza; Nikkhah, Homayoon; Nasri Razin, Bahram (Novelty in Biomedicine, 2014)
A 35-year-old lady presented with a history of decreased vision in her right eye from one week before her referral. She did not report any significant systemic disease. Ocular findings were compatible with the diagnosis of central retinal vein occlusion. Systemic laboratory tests were all within normal limits except for Mantoux test (PPD) which was positive, 18 mm induration and 2+ redness. Chest radiography was negative for lung tuberculosis. Fluorescein angiography confirmed the presence of retinal vasculitis. With a probable diagnosis of papillophlebitis secondary to tuberculosis, the patient received a course of anti-tuberculosis medications. The inflammation subsided and vision improved within a 6-months therapy. This was a rare case of presumed ocular tuberculosis with no evidence of systemic infection presenting first as a papillophlebitis.